Evaluation of Community Empowerment Initiatives in Dengue Hemorrhagic Fever Control and Prevention in Pekanbaru City: English - Lubis, Arga Abdi Rafiud Darajat; Agung, Vaqqi Riehanda; Lubis, Satia Negara (Asian Multidisciplinary Research Journal of Economy and Learning, 2024)
This study aimed to evaluate the use of community empowerment strategies in dengue fever prevention and control in Pekanbaru City, with a focus on program inputs, outputs, and processes in relation to regional planning. Utilizing qualitative methods, the study relied heavily on informants to shape its findings. The "one house one jumantik" initiative encountered significant challenges due to limited funding and funds being redirected for Covid-19 management. Additionally, the facilities and infrastructure in Limapuluh District were found to be inadequate. Despite improvements in dengue fever incidence rates, the ABJ (Larva Free Rate) in Limapuluh and Sail Districts failed to meet the Indonesian Ministry of Health's target of ≥ 95%.